Pengaruh Gaya Belajar dan Teman Sebaya Terhadap Hasil Belajar Mata Pelajaran Ekonomi Kelas XI IPA SMA Negeri 2 Muaro Jambi - Devina, Silvia; Sembiring, Benar (SJEE (Scientific Journals of Economic Education), 2024)
This research aims to determine the influence of learning styles and peers on economics subjects in class XI Science at SMA Negeri 2 Muaro Jambi. The research method used in this research is a quantitative method using simple linear regression analysis techniques. The results of the research show that there is a positive influence of learning styles and peers on learning outcomes for students in class XI Science at SMA Negeri 2 Muaro Jambi. So, this means that if students are given lessons according to their learning style and the better their peers, the better the students' learning outcomes will be.